Tropical Andean forests are highly susceptible to nutrient inputs--rapid effects of experimental N and P addition to an Ecuadorian montane forest. - Jürgen Homeier; Dietrich Hertel; Tessa Camenzind; Nixon L Cumbicus; Mark Maraun; Guntars O Martinson; L Nohemy Poma; Matthias C Rillig; Dorothee Sandmann; Stefan Scheu; Edzo Veldkamp; Wolfgang Wilcke; et al. (PLoS ONE, 2012)
Tropical regions are facing increasing atmospheric inputs of nutrients, which will have unknown consequences for the structure and functioning of these systems. Here, we show that Neotropical montane rainforests respond rapidly to moderate additions of N (50 kg ha(-1) yr(-1)) and P (10 kg ha(-1) yr(-1)). Monitoring of nutrient fluxes demonstrated that the majority of added nutrients remained in the system, in either soil or vegetation. N and P additions led to not only an increase in foliar N and P concentrations, but also altered soil microbial biomass, standing fine root biomass, stem growth, and litterfall. The different effects suggest that trees are primarily limited by P, whereas some processes-notably aboveground productivity--are limited by both N and P. Highly variable and partly contrasting responses of different tree species suggest marked changes in species composition and diversity of these forests by nutrient inputs in the long term. The unexpectedly fast response of the ecosystem to moderate nutrient additions suggests high vulnerability of tropical montane forests to the expected increase in nutrient inputs.